Hemodynamics during transcatheter aortic valve implantation in patients with severe aortic stenosis measured by invasive pressure volume loop analysis. (25th November 2020) - Seppelt, P.C; De Rosa, R; Mas-Peiro, S; Murray, I; Zeiher, A.M; Fichtlscherer, S; Vasa-Nicotera, M
Abstract: Introduction: Transcatheter aortic valve implantation (TAVI) for a stenotic aortic valve reduces the ventricular to aortic gradient and is expected to improve diastolic and systolic left ventricular function over the long-term. However, information about the early hemodynamic changes are lacking. To address this open question, we performed invasive pressure volume loop analysis prior and immediately after TAVI. Methods: Invasive left ventricular pressure volume loop analysis was performed in 8 patients with aortic stenosis (mean 81.3 years) prior and immediately after transfemoral TAVI (conductance catheter). Parameters for global hemodynamics, afterload, contractility and the interaction of the cardiovascular system were analyzed. Results: After TAVI, left ventricular ejection fraction (53.9% vs. 44.8%, p=0.018) as well as parameters for myocardial contractility such as preload recruitable stroke work (68.5 vs. 44.8mmHg, p=0.012) and endsystolic elastance (3.55 vs. 2.17, p=0.036) declined significantly compared to baseline. As sign of impaired diastolic function, TAU, a preload-independent measure of isovolumic relaxation (37.3 vs. 41.8ms, p=0.018) and enddiastolic pressure (13.1 vs. 16.4mmHg, p=0.015) increased after valve implantation. Contrarily, decreased ventricular-arterial coupling indicated early improvements in global cardiovascular energy efficiency (1.40 vs. 0.97 p=0.036). Arterial elastance had a strong correlation with the number of conducted rapid ventricular pacings (Pearson correlation coefficient, 0.772, p=0.025). Conclusion: Invasive left ventricular pressure volume loop analysis revealed impaired systolic and diastolic function in the early phase after TAVI in patients with severe aortic stenosis. Contrarily, decreased ventricular-arterial indicated early improvement of global cardiovascular energy efficiency. Funding Acknowledgement: Type of funding source: None